Construction of Pendant‐Armed Schiff‐Base Macrocyclic Dinuclear Zinc Complexes and Their Selective Recognition of Acetate Ions. Issue 9 (13th July 2014) - Zhang, Kun; Jin, Chao; Chen, Hui‐Qing; Yin, Gui; Huang, Wei
Abstract Two new flexible extended dialdehydes (H2hpdd and H2pdd) with different functional pendant arms (CH2CH2PhOH and CH2CH2Ph) have been synthesized and reacted with 1, 2‐bis(2‐aminoethoxy)ethane to prepare Schiff‐base macrocyclic complexes in the presence of a ZnII‐ion template. As a result, two preorganized dinuclear ZnII intermediates (1 and 2), as well as two 42‐membered folded [2+2] macrocyclic dinuclear ZnII complexes (3 and 4), were produced. The central zinc ions in compounds 1, 2, 3, 4 showed distinguishable coordination patterns with the dialdehydes and the [2+2] macrocyclic ligands, in which a subtle pH‐adjustment function of the two pendant arms (with or without the phenolic hydroxy group) was believed to play a vital role. Furthermore, cation‐ and anion‐recognition experiments for complexes 3 and 4 revealed that they could selectively recognize acetate ions by the formation of 1:1 stoichiometric complexes, as verified by changes in their UV/Vis and MS (ESI) spectra and even by the naked eye.